Clinical Implication of Patchy Pattern Corneal Staining in Dry Eye Disease - Seitaro Komai; Norihiko Yokoi; Hiroaki Kato; Aoi Komuro; Yukiko Sonomura; Shigeru Kinoshita; Chie Sotozono (Diagnostics, 2021)
Corneal fluorescein staining in a form that is commonly called a “patchy pattern (PP)” is sometimes seen with or without superficial punctate keratopathy (SPK) in dry-eye diseases (DEDs). Here, we investigated the differences in the clinical features of DED patients with and without PP corneal staining (PPCS). This study involved 35 DEDs with PPCS (PPCS group) and 30 DEDs with SPK and without PPCS (non-PPCS group). The tear meniscus radius (TMR, mm), spread grade (SG) of the tear-film lipid layer (i.e., SG 1–5, 1 being best), noninvasive breakup time (NIBUT, seconds), fluorescein breakup time (FBUT, seconds), corneal epithelial damage (CED, 15 points maximum), conjunctival epithelial damage (CjED, six points maximum), the Schirmer’s 1 test (ST1, mm), and the prevalence of Sjögren’s syndrome (SS) were examined, and then compared between the two groups. Our findings revealed that between the groups (PPCS vs. non-PPCS), there was a statistically significant difference (p < 0.05) in CjED (3.1 ± 1.9 vs. 1.3 ± 1.6), ST1 (5.6 ± 7.4 vs. 14.8 ± 11.4), and the prevalence of SS (60.0% vs. 16.7%). Our findings suggest that DEDs and dry-eye patients with PPCS may indicate not only SS itself, but also the ophthalmological characteristics compatible with SS.